PENGALAMAN KOMUNIKASI MAHASISWI YANG MELAKUKAN HIJRAH (STUDI FENOMENOLOGI PADA MAHASISWI FISIP UNIVERSITAS RIAU YANG MELAKUKAN HIJRAH) - Winda Ersa Putri; Muhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The rapid development of Islamic religious knowledge led to the phenomenon of doing hijrah among female students, especially female students at FISIP University of Riau campus. There are many female students in FISIP who change their appearance to be syar'i even use veil and have been able to leave bad behavior become muslimah's female student. This study aims to find out how the motives, meaning of hijrah and communication experience of student who did hijrah in FISIP University of Riau.This research uses qualitative research method with phenomenology approach. The research subjects amounted of seven female students of FISIP Universitas Riau chosen by using purposive technique. Data collection is done through in-depth interviews, observation and documentation. To perform the validity of data, the authors use the technique of diligence observation and reverensi adequacy.The results showed that the motives of FISIP students who do hijrah consists of because motive, that includes self muhasabah, getting hidayah, parents, and environment and in order to motive include get Allah blessing, motivate others and istiqomah. The meanings of hijrah are divided into four categories and all of which leads to personal change better. The pleasant communication experience that is, (1) have a solehah friends, (2) can give motivation, (3) intense with family, (4) have positive image and (5) got good attitude in interaction and unpleasant communication that is, (1) getting negative comments, (2) shunned by friends, (3) experiencing various obstacles, (4) getting temptations, (5) getting unpleasant treatment, based on their interactions with their family's, friends, and their environment's.Keyword: Experience, Communication, Communication experience, Hijrah.